Future of plant biotechnology in crop improvement - Agrawal, Vishwanath P. (Himalayan Journal of Sciences, 2006)
Cultivation of crops having multiple durable resistance to diseases and pests will be made easier by plant biotechnology. Transgenes and marker-assisted selection will aid in the development of high yielding crops, which will be needed to feed the world and save land for the conservation of plant biodiversity in natural habitats. The genetic base of crop production will be conserved and further widened by the integration of biotechnology tools in conventional breeding. Utilization of specific genotypes to particular cropping systems will be facilitated. Value-added high quality crops will be obtained through multidisciplinary collaboration among plant breeders, biotechnologists, natural product chemists and other plant scientists. Himalayan Journal of Sciences 1(1): 17-20, 2003